2020
DOI: 10.3389/fsurg.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Giant Ovarian Cysts Using the Alexis Laparoscopic System®: A Case Series

Abstract: The aim of this study was to review the characteristics of patients who underwent laparoscopic removal of giant ovarian cysts using the Alexis Laparoscopic System® and confirm the safety and feasibility of this technique. Method:We conducted a retrospective review of data of women undergoing the procedure from March 2014 to February 2019. Inclusion criteria were ovarian cysts of at least 15 cm. Exclusion criteria were the presence of solid components and suspicion of neoplasia on imaging.Results: Six patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Another laparoscopic approach used by Coccia et al involved puncturing the cyst wall with a 5-mm trocar and aspirating the cyst under direct visualization with a suction irrigator while maintaining application of the cyst to the abdominal wall with forceps [9]. More recently, surgeons have described use of the Alexis laparoscopic system ® , with demonstration in a case series of six patients with masses up to 30 cm in diameter [10]. After making an initial abdominal incision ranging in size from 2.5 to 4 cm, a small Alexis ® retractor was inserted into the abdomen, the cyst was punctured with the trocar, liquid evacuated after trocar insertion into the mass, and the puncture site closed with an Endoloop ® ligature.…”
Section: Discussionmentioning
confidence: 99%
“…Another laparoscopic approach used by Coccia et al involved puncturing the cyst wall with a 5-mm trocar and aspirating the cyst under direct visualization with a suction irrigator while maintaining application of the cyst to the abdominal wall with forceps [9]. More recently, surgeons have described use of the Alexis laparoscopic system ® , with demonstration in a case series of six patients with masses up to 30 cm in diameter [10]. After making an initial abdominal incision ranging in size from 2.5 to 4 cm, a small Alexis ® retractor was inserted into the abdomen, the cyst was punctured with the trocar, liquid evacuated after trocar insertion into the mass, and the puncture site closed with an Endoloop ® ligature.…”
Section: Discussionmentioning
confidence: 99%
“…The wound retractor, in our case series, was covered with a surgical glove and the cap closed to avoid air leakage during laparoscopy. Other authors have reported that a laparoscopic cap was put on to create and maintain pneumoperitoneum at the laparoscopy ( 8 ). The combination of laparoscopic observation and subsequent release of the adhesion may be useful in avoiding laparotomy conversion in cases of adhesion between the cyst and pelvic walls or other intraperitoneal organs.…”
Section: Discussionmentioning
confidence: 99%
“…A dermoid cyst subgroup analysis highlighted a significant correlation between cyst rupture and chemical peritonitis (risk rate: 9.36; 95% confidence interval: 1.20-73.28) [ 13 ]. Introducing novel techniques, such as using a single port over a three port in laparoscopy, will significantly impact the rupture risk (3.0 vs. 22.2%); however, there will be no variations in postoperative complications [ 14 ]. The spillage of cystic contents can be prevented by covering the cyst first with a sterilized surgical sheet applied with quick-drying glue and then puncturing.…”
Section: Discussionmentioning
confidence: 99%